Macronutrient balance has opposing effects on cognition and survival in honey bees. (19th July 2022) - Bouchebti, Sofia; Wright, Geraldine A.; Shafir, Sharoni
Abstract: Malnutrition in vertebrates, including humans, is known to affect brain development. Protein deprivation in the early stages of life dramatically impairs cognitive abilities. In insects, dietary protein deficiency influences several physiological and behavioural traits, but it is unknown how protein to carbohydrate (P:C) ratio simultaneously affects survival and cognitive performance. We used the geometric framework approach to examine the effects of P:C ratio in the diet of newly emerged honey bees on their survival, sucrose sensitivity, and learning and memory by conditioning of the proboscis extension response. The P:C ratio in the diet did not affect sucrose sensitivity, whereas it affected lifespan and cognition differently. While lifespan peaked at P:C ratio of 1:19, learning and short‐term memory peaked at P:C ratios of 1:9 and 1:4. Protein deprivation slightly reduced bee lifespan but highly impaired learning and short‐term memory. On the other hand, an excess of protein dramatically reduced bee lifespan with lesser effects on learning and short‐term memory. Bees were only able to form an early long‐term memory when they had been eating a protein diet (P:C ratio of 1:9) during 24 hr before the test, regardless of the diet eaten previously. Our study shows that nutrition affects honey bee cognitive abilities, but that these effects, unlike in vertebrates, can be quickly reversed with an appropriate diet. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.